Impulse Buying Behavior of Consumers Through Social Commerce in Ho Chi Minh City - Nguyen Thi Hai Binh (ZBW - Leibniz Information Centre for Economics, 2024)
Purchasing through social commerce has become increasingly popular in recent years. Multiple papers have been conducted to examine customer purchasing behavior on social commerce platforms. Nevertheless, this study has restrictions in its applicability to poor nations and exclusively focuses on those who are employed. Currently, there is a lack of research papers specifically addressing the topic of consumers as possible viewers who are exposed to social commerce. This study aims to examine the variables that contribute to consumers' impulsive purchase behavior. Specifically, it focuses on identifying the factors that impact impulsive buying behavior among consumers. The development of my conceptual framework was based on the integration of two theories: The Unified Theory of Acceptance and Use of Technology (UTAUT) and the Theory of Planned Behavior (TPB). Hence, non-probability sampling was selected for this investigation. Data was obtained from consumers who had made purchases on social commerce platforms using a questionnaire. The purpose was to investigate the components that influence consumers' behavioral intentions, including social influence (SI), behavior (AB), subjective norms (SNB), and behavioral control (BC). The findings indicate that several factors have a favorable impact on behavioral intention subsequently affect impulse buying behavior. The findings obtained from employing the PLS-SEM approach unambiguously demonstrated the impact of the components under investigation and conclusively indicated that SNB was not substantiated in this study.
Keywords: 330; Social commerce; Impulse buying; Consumers